2010
DOI: 10.2353/ajpath.2010.090242
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor Inhibits Lysosomal Degradation of Bcl-xL and Apoptosis in HepG2 cells

Abstract: Pigment epithelium-derived factor (PEDF) has several biological actions on tumor cells , but its effects are cell-type dependent. The aim of this study was to examine the pathophysiological role of PEDF in hepatocellular carcinoma (HCC). PEDF expression was examined in various hepatoma cell lines and human HCC tissues , and was seen in various hepatoma cell lines including HepG2 cells. In human HCC tissues, PEDF expression was higher than in adjacent non-HCC tissues. In addition , serum PEDF levels were higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…11,15,16 Conversely, it exerts anti-apoptotic effects on neuronal or hepatoma cells by activating the nuclear factor-κB signaling cascade or inhibiting lysosomal Bcl-xL degradation, respectively. 15,16,20 It can also inhibit platelet-derived growth factor-induced VSMC proliferation and migration by blocking reactive oxygen species generation, 18 although we recently demonstrated that PEDF stimulated both proliferation and migration of retinal pigment epithelial cells in a laser-induced choroidal neovascularization model. 21 It is speculated that the elusive functions of PEDF may attribute to multiple unknown receptors, the immediate cellular state, as well as pathologic signals and factors present in the cellular microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,16 Conversely, it exerts anti-apoptotic effects on neuronal or hepatoma cells by activating the nuclear factor-κB signaling cascade or inhibiting lysosomal Bcl-xL degradation, respectively. 15,16,20 It can also inhibit platelet-derived growth factor-induced VSMC proliferation and migration by blocking reactive oxygen species generation, 18 although we recently demonstrated that PEDF stimulated both proliferation and migration of retinal pigment epithelial cells in a laser-induced choroidal neovascularization model. 21 It is speculated that the elusive functions of PEDF may attribute to multiple unknown receptors, the immediate cellular state, as well as pathologic signals and factors present in the cellular microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an earlier report showing that the serum concentration of PEDF was decreased in patients with cirrhosis and HCC relative to healthy individuals and to patients with chronic hepatitis 139 , recent results showed that PEDF levels were higher in HCC than in adjacent normal tissues and also greater in serum samples from patients with HCC than normal controls. They also showed that the effective treatment of HCC caused significant reductions in serum PEDF levels 140 . Although this apparent discrepancy may be due to organ- or tissue-specific differences, the overwhelming evidence supports the notion that the lower the tumour PEDF levels, the poorer the prognosis and the worse the expected outcome.…”
Section: Pedf Cancer Prognosis and Therapeutic Potentialmentioning
confidence: 99%
“…PEDF is an endogenous inhibitor of angiogenesis and is neuroprotective. It inhibits the migration of EC in response to proangiogenic factors (10) and induces apoptosis of human EC by activating p38 mitogen-activated protein kinase and caspases (5,22). Increased PEDF expression in the retina results in attenuation of neovascularization through modulation of canonical Wnt signaling (30).…”
mentioning
confidence: 98%
“…PEDF is also expressed in other ocular cell types, including Müller cells, pericytes, and EC (40). PEDF influences the function and pathogenesis of various tissues, including liver, kidney, heart, prostate, and lung, due to its various biological activities (8,12,22,43). PEDF is an endogenous inhibitor of angiogenesis and is neuroprotective.…”
mentioning
confidence: 98%